2020
DOI: 10.1088/1755-1315/497/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity of Arabica coffee [Coffea arabica L.] in Solok Regency by SRAP molecular markers

Abstract: Coffee is one of the most widely grown plantation crops in Indonesia. There are two types of coffee plants that are most widely cultivated, namely Robusta and Arabica which are distributed in several provinces including West Sumatra. Solok Regency is one of the coffee production centers in West Sumatra. Information regarding the genetic diversity of Arabica coffee that scattered in several locations is still not available. Due to this fact, the genetic diversity of coffee can be identified by DNA analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Similar results were reported previously by (Aga et al, 2003;Tesfaye et al, 2014) using ISSR markers, where coffee tree samples comprising forest, semi-forest and farmers' cultivars collected from different parts of Ethiopia were clustered based on their geographic origin. Such results were also reported from Indonesia, where 73 to 92 % genetic similarity was detected by eight SRAP markers in populations of five arabica coffee varieties collected from different locations (Yunita et al, 2020). This indicates that some genotypes from the same geographic origin are more closely related at the DNA level than those from different origins.…”
Section: Clustering Patterns Of Elite Breeding Linessupporting
confidence: 80%
“…Similar results were reported previously by (Aga et al, 2003;Tesfaye et al, 2014) using ISSR markers, where coffee tree samples comprising forest, semi-forest and farmers' cultivars collected from different parts of Ethiopia were clustered based on their geographic origin. Such results were also reported from Indonesia, where 73 to 92 % genetic similarity was detected by eight SRAP markers in populations of five arabica coffee varieties collected from different locations (Yunita et al, 2020). This indicates that some genotypes from the same geographic origin are more closely related at the DNA level than those from different origins.…”
Section: Clustering Patterns Of Elite Breeding Linessupporting
confidence: 80%
“…The genetic variability of C. arabica accessions from other countries, such as Costa Rica [94], Mexico [95], Nicaragua [96], India [97][98][99], Indonesia [100], China [101], Kenya [102] and Ethiopia [34,[103][104][105], has also been analyzed using markers such as ISSRs, SSRs, sequence-related amplified polymorphisms (SRAPs), AFLPs, and SNPs. In Ethiopia, different studies have shown the presence of great genetic variability in coffee plants.…”
Section: Genetic Diversity Based On Molecular Markersmentioning
confidence: 99%